2013
DOI: 10.3342/ceo.2013.6.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Dysphonia after Laryngomicrosurgery for Benign Vocal Fold Disease

Abstract: ObjectivesLaryngomicrosurgery (LMS) is used to manage most vocal fold lesions. However, the functional voice outcome of the LMS might be diverse due to the influence of various factors. We intend to evaluate the incidence and etiologic factors of persistent dysphonia after LMS for benign vocal fold disease (BVFD).MethodsWe performed a retrospective review of 755 patients who underwent LMS for BVFD. We analyzed the clinical characteristics, preoperative and postoperative two onths voice studies. Postsurgical dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…9 Analysis of diagnosis showed majority 26% were having vocal cord nodule which is in accordance with the study done by Shin, Chang and Yang showed 20% having vocal cord nodule. 10 Our study showed 58% of patients having vocal cord nodule in 4 th and 5 th decade. It is observed that vocal cord nodules were common in patients having voice abuse.…”
Section: Discussionmentioning
confidence: 55%
“…9 Analysis of diagnosis showed majority 26% were having vocal cord nodule which is in accordance with the study done by Shin, Chang and Yang showed 20% having vocal cord nodule. 10 Our study showed 58% of patients having vocal cord nodule in 4 th and 5 th decade. It is observed that vocal cord nodules were common in patients having voice abuse.…”
Section: Discussionmentioning
confidence: 55%
“…GRBAS is a clinician-based acoustic assessment protocol used by a speech pathologist and not the surgeon to assess the speech quality of a sustained utterance of the vowel "a" before and after surgery in a soundproof room at the voice center [17]. It was used for the perceptual voice analysis by a speech pathologist before and after surgery.…”
Section: Grade Roughness Breathiness Asthenia and Strain Scale (Grbas)mentioning
confidence: 99%
“…Supplementary Table 2 shows the intraoperative cuff pressures. The median (IQR) cuff pressures (mm Hg) were significantly lower for the tapered cuff than for the control cuff after tracheal intubation [9 (7-12) vs. 11 (8)(9)(10)(11)(12)(13)(14); P = 0.009)], after neck extension [9 (7-12) vs. 12 (10-15); P < 0.001] and after retraction [18 (15-23) vs. 25 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31); P = 0.007, Figure 3A]. Pressure differentials (i.e., pre-post change) caused by surgical retraction and pressure adjustment were smaller in the tapered group than in the control group (Figure 3D).…”
Section: Intraoperative Cuff Pressure and The Need For Pressure Adjus...mentioning
confidence: 99%